The structure of the co-orbital stable regions as a function of the mass ratio - Liberato, L. [UNESP]; Winter, O. C. [UNESP] (Oxford University Press (OUP), 2020)
Although the search for extrasolar co-orbital bodies has not had success so far, it is believed that they must be as common as they are in the Solar system. Co-orbital systems have been widely studied, and there are several works on stability and even on formation. However, for the size and location of the stable regions, authors usually describe their results but do not provide a way to find them without numerical simulations, and, in most cases, the mass ratio value range is small. In this work, we study the structure of co-orbital stable regions for a wide range of mass ratio systems and build empirical equations to describe them. It allows estimating the size and location of co-orbital stable regions from a few system parameters. Thousands of massless particles were distributed in the co-orbital region of a massive secondary body and numerically simulated for a wide range of mass ratios (μ) adopting the planar circular restricted three-body problem. The results show that the upper limit of horseshoe regions is between 9.539 × 10−4 < μ < 1.192 × 10−3, which corresponds to a minimum angular distance from the secondary body to the separatrix of between 27.239o and 27.802o. We also found that the limit to existence of stability in the co-orbital region is about μ = 2.3313 × 10−2, much smaller than the value predicted by the linear theory. Polynomial functions to describe the stable region parameters were found, and they represent estimates of the angular and radial widths of the co-orbital stable regions for any system with 9.547 × 10−5 ≤ μ ≤ 2.331 × 10−2
Keywords: Celestial mechanics; Methods: numerical; Minor planets, asteroids: general; Planets and satellites: dynamical evolution and stability